How Fast Are the Asian Countries Progressing Toward Green Economy? Implications for Public Health - Ming Shao; Hui Jin; Fu-Sheng Tsai; Fu-Sheng Tsai; Fu-Sheng Tsai; Fu-Sheng Tsai; Mihajlo Jakovljevic; Mihajlo Jakovljevic (Frontiers Media S.A., 2022)
Monitoring progress toward green economy has been a key policy focus globally. The purpose of our study is to assess Asian countries' green development performance and also the progress toward green economy overtime. To achieve this goal, we propose a green development index (GDI) to assess the level and ranking of green development for Asian countries, and then we measure the progress toward green economy by the method based on the compound annual growth rate (CAGR). The result shows that the northeast Asian countries together with Singapore and Israel are leaders in green development performance across Asia, but the most progress toward green economy has been achieved by some medium green development level countries, like China. Countries with the fastest movement away from green economy are some laggard countries with poor green development performance, such as Syria and Yemen. More generally, the leading countries have reached a high green development level, and the medium ones move fast toward green economy, whereas some laggards get worse. We also discuss the implications for public health in environmental protection, green consumption, and green production.